Progress in magnetic resonance imaging of the glymphatic system - Jinhao Lyu; Xinyu Wang; Qi Duan; Wanbing Wang; Runze Li; Xiaoyu Wang; Xin Lou (Magnetic Resonance Letters)
The glymphatic system (GS) is a newly discovered brain anatomy. Its discovery improves our understanding of brain fluid flow and waste removal paths and provides an anatomical basis for the flow of cerebral interstitial fluid (ISF) and cerebrospinal fluid (CSF). GS occurs through a normal exchange within perivascular space (PVS), facilitating the elimination of metabolic wastes generated by nerve cells from the brain. Therefore, the GS is mainly responsible for the removal of metabolic waste. Reduced GS activity has been observed to be associated with central nervous system disorders such as cerebral small vessel disease (CSVD) and neurodegenerative diseases. Its activity is expected to be an indicator for diagnosing diseases and predicting their prognosis. This review introduces the magnetic resonance imaging (MRI) technology related to the GS suitable for clinical use and the difference in the system's activity in normal and abnormal states. Through a summary of previous research, imaging methods suitable for monitoring the activity of the GS in the clinic were proposed, and their diagnostic effect on different brain disorders was analyzed. This review aims to clarify ideas for the clinical translation of basic research focusing on GS and provide future clinical research directions and perspectives.